The Artistry and Beauty of Coastal Batik: The Unique Identity and Significance of Lasem Batik - Suminto, RA Sekartaji (UPT Pusat Penerbitan LP2MPP ISI Bali, 2023)
This research aims to explore and highlight the cultural significance of Batik in the Indonesian archipelago, highlighting the unique characteristics of Batik Lasem as a renowned coastal batik variety. The study involves extensive research and documentation of the cultural heritage of Batik, focusing on Batik Lasem. Various historical records, literature, and cultural resources were reviewed and analyzed to gather comprehensive information. The research findings underscore the intrinsic value of Batik as an enduring cultural tradition in Indonesia. Batik Lasem, with its distinct features such as the use of the rare